Distribution of bacterial populations in a stratified fjord (Mariager Fjord, Denmark) quantified by in situ hybridization and related to chemical gradients in the water column. - Ramsing, N B (1996)
The vertical distribution of major and intermediate electron acceptors and donors was measured in a shallow stratified fjord. Peaks of zero valence sulfur, Mn(IV), and Fe(III) were observed in the chemocline separating oxic surface waters from sulfidic and anoxic bottom waters. The vertical fluxes of electron acceptors and donors (principally O2 and H2S) balanced within 5%; however, the zones of oxygen reduction and sulfide oxidation were clearly separated. The pathway of electron transfer between O2 and H2S was not apparent from the distribution of sulfur, nitrogen, or metal compounds investigated. The chemical zonation was related to bacterial populations as detected by ethidium bromide (EtBr) staining and by in situ hybridization with fluorescent oligonucleotide probes of increasing specificity. About half of all EtBr-stained cells were detectable with a general oligonucleotide probe for all eubacteria when digital image analysis algorithms were used to improve sensitivity. Both EtBr staining and hybridization indicated a surprisingly uniform distribution of bacteria throughout the water column. However, the average cell size and staining intensity as well as the abundance of different morphotypes changed markedly within the chemocline. The constant overall cell counts thus concealed pronounced population shifts within the water column. Cells stained with a delta 385 probe (presumably sulfate-reducing bacteria) were detected at the chemocline at about 5 x 10(4) cells per ml, and this concentration increased to 2 x 10(5) cells per ml beneath the chemocline. A long slim rod-shaped bacterium was found in large numbers in the oxic part of the chemocline, whereas large ellipsoid cells dominated at greater depth. Application of selective probes for known genera of sulfate-reducing bacteria gave only low cell counts, and thus it was not possible to identify the dominant morphotypes of the sulfate-reducing community.